AGRIBUSINESS SYSTEM AND LOCAL WISDOM IN FULFILLING FOOD OF FISHERMEN'S COMMUNITY IN LONTAR VILLAGE, SERANG REGENCY - Sutisna, Tatang; Widiati, Siti (Journal of Agri Socio Economics and Business, 2024)
This research aimed to analyse the agribusiness system and local wisdom in the fulfilment of food, and the mechanism for meeting the food needs of fishermen households in Lontar Village, Tirtayasa District, Serang Regency. Direct interviews were conducted with fishermen living in the coastal area of Lontar Village who are members of the Joint Business Group using a list of questions. The data was analysed using the Food Coping Strategy Index to study the mechanism of fishermen's households for meeting their food needs to increase food security. The research results showed that fishermen's households in Lontar Village rely on coastal agriculture and fisheries business diversification as the main strategy for filling food needs. Based on the Food Coping Strategy analysis, fishermen's households implemented mechanisms to face the crisis with defensive behavior to meet food needs from Level I to Level III. This defensive behavior is dominated by efforts in Phase I, such as looking for a side job (61.11%), gardening (33.33%), raising goats (44.44%), reducing the type of food consumed (66.67%), and reducing meal frequency by 50% of households. On the other hand, the behavior of often using their savings to buy food dominated level II by 16.65%, borrowing money from close relatives by 55.56% and buying food needs by paying later as much as 22.22% of households. Stage III was carried out with migration to cities and abroad by 66.67% of households.